A new genus and species of worm eels, Sympenchelys taiwanensis (Anguilliformes: Ophichthidae: Myrophinae), from the northwestern Pacific Ocean - Hibino, Yusuke; Ho, Hsuan-Ching; Kimura, Seishi (Zootaxa, 2015)
A new genus and species of ophichthid eel, Sympenchelys taiwanensis is described. The genus is distinguishable from all other myrophine genera by having neural and haemal spines with well-developed paddle-like tips, and from two closely similar genera, Mureaenichthys Bleeker 1853 and Skythrenchelys Castle & McCosker 1999, by the following combination of characters: an unconstricted gill opening; a minute flap just posterior to the gill opening; a slender cleithrum; three preopercular pores; a slender and distinctly tapered maxilla; an undeveloped supraoccipital crest; and large and recurved teeth on jaws and vomer. Sympenchelys taiwanensis is described from five specimens collected from Taiwan, the northwestern Pacific Ocean.